Dental healthcare worker’s knowledge and attitude on hepatitis B infection and their uptake of hepatitis B vaccination at a tertiary care center in Nepal - Gurung, Deepa; Chaudhary, Bikash; Joshi, Ujjwal; Shrestha, Manash (Journal of Chitwan Medical College, 2021)
Background: Hepatitis B is a serious public health problem and dental healthcare workers (HCW) are at a greater risk of acquiring the infection. The main aim of this study was to assess the knowledge, attitude, and hepatitis B vaccination status of dental HCW at a tertiary dental hospital. Methods: A cross-sectional study was carried out among all dental HCW and their knowledge level, attitude, and vaccine uptake were measured. Factors associated with the receipt of full hepatitis B vaccination was assessed using Pearson’s chi-square test. The data was analyzed using Statistical Package for the Social Sciences version 23. Results: Out of the total 254 dental HCW, 207 responded to the survey signifying a response rate of 81.5%. The mean age of the participants was 25.6±5.4 years. A majority of the participants were female (156; 75.4%), unmarried (169; 81.6%), and dental students (117; 56.5%). Most participants had a fair knowledge (117; 56.5%) and a positive attitude regarding Hepatitis B virus (189; 91.3%). However, the uptake of full dose of hepatitis B vaccine was only 41.5%. Dental HCW’s age, marital status, educational attainment, and type of dental HCW were associated with receipt of full vaccination (all p-value <0.05). Conclusions: Despite fair knowledge and positive attitude, the uptake of full vaccination was low among the dental HCW. Further strategies are needed to improve the hepatitis B vaccine uptake. Specifically, increasing the access